UPAYA SUPERVISOR MENJAGA KUALITAS PELAYANAN PRAMUSAJI DI RESTORAN EDEN HOOKAH CLUB KUTA BALI SAAT PANDEMI COVID-19 - Sumerta, I Ketut Eli Sumerta; Palentina, I Gusti Ayu; Budiasa, I Ketut (Universitas Triatma Mulya, 2022)
This research is entitled the supervisor's efforts to maintain the quality of waiter service at Eden Hookah Club Bali Kuta Restaurant during the Covid-19 Pandemic. Knowledge found by the Supervisor on waitress services during the COVID-19 pandemic. The data used in this study was qualitative obtained from data sources primary and secondary. Data collection techniques by means of observation, interviews and documentation. The analysis technique was carried out by means of qualitative descriptive. From the results of the research and discussion, it can be concluded as follows: the obstacles faced by supervisors in maintaining service quality are the lack of awareness of waiters on the importance of using masks, always washing hands, maintaining distance, maintaining cleanliness and maintaining body hygiene in accordance with the maximum limit that has been determined. Efforts are made to always remind the use of masks for both waiters and guests who come to the restaurant, increase hand sanitizer in the restaurant area such as at tables and in front of the entrance, routinely clean the restaurant by wiping tables and chairs and spraying disinfectant in the restaurant area, checking the body temperature of the waiter before entering the restaurant, and maintain a distance.